The Effect of Possible Sentence Strategy on Students in The Eighth Grades's Abilty to Master Vocabulary - Yaredi Waruwu; Afore Tahir Harefa (Universitas Nias, 2023)
The goal of the study was to determine whether the Possible Sentences Strategy had a substantial impact on eighth-graders ability to master vocabulary. A quasi-experimental design was used for the study. There were 82 pupils in the eighth population of the study. Then, using the Cluster Sampling Technique, the researcher chose the study's sample, which included 60 pupils. The researcher conducted pre-tests in the control and experimental groups before beginning therapy. The control group's mean score was 56.50 with a L count of 0.1269, while the experimental group's mean score was 51 with a L count of 0.1403 and a L table of 0.16. As a result, the pre-test results for the experimental group and control group were reported as having a Normal Distribution. The next step was to look at uniformity. F table = 1.86 and F count = 1.09, according to pre-test computation. A homogenous pre-test result was reported. In both the control and experimental groups, the researcher conducted a post-test after the therapy. The experimental group's mean score was 80.83 while the control group's mean score was 64 with a L count of 0.1032 and a L table of 0.1545. The post-test findings of the control and experimental groups were thus reported as having a Normal Distribution. The next step was to look at uniformity. F count = 1.45 and F table = 1.86 were calculated based on the post-test results. A homogenous post-test result was reported. A hypothesis test was then conducted by the researcher. Table was obtained as follows: t1/2(dk) = t0.025(72) = -2.002; t count = 4.98. It means that t count (4.98) did not exist between interval -2.002 to 2.002 (-2.002 ≤ t ≤ 2.002). So, it can be concluded that there is a significant effect of the Possible Sentences Strategy on the students’ ability to Mastering Vocabulary.